A cost benefit analysis for industry 4.0 in a job shop environment using a mixed integer linear programming model. (April 2021) - Alami, Darwish; ElMaraghy, Waguih
Highlights: A new costing mathematical model is introduced using Activity Based Costing. A cost benefit mathematical model for industry 4.0 is introduced to link suppliers. The model considers the bi-directional relationship between annual hours and the hourly rate. Interconnecting suppliers increases agility and responsiveness. A decrease in profit by 0.094% when investing to link suppliers. Abstract: As the manufacturing industry is approaching implementation of the 4th industrial revolution, changes will be required in terms of scheduling, production planning and control as well as cost-accounting departments. Industry 4.0 promotes decentralized production and hence, cost models are required to capture costs of products and jobs within the production network considering the utilized manufacturing system paradigm A new mathematical cost model is proposed for assessing the cost-benefit analysis of introducing Industry 4.0 elements to the manufacturing facility, specifically, integrating and connecting external suppliers as strategic partners and establishing an infrastructure for communicating information between the manufacturing company and its strategic suppliers. The mathematical model takes into consideration the bi-directional relationship between hourly rates and total hours assigned to workcentres/activities in a certain production period. A case study, from a multinational machine builder, is developed and solved using the proposed model. Results suggest that though an additional cost is required to establish infrastructure to connect suppliers, the responsiveness and agility achieved resulting from uncertainty outweighs the additional cost.